Effect of hormonal treatment on induction of estrus and plasma mineral composition in true anestrus buffalo heifers - MAVI, P S; BAHGA, C S; SINGH, NARINDER; CHEEMA, R (The Indian Journal of Animal Reproduction, 2023)
Eight true anoestrus mature Murrah buffalo heifers aged 3-4 years and weighing 300-325 kg wererandomly divided into two groups. Group 1 was injected with 100 mg progesterone (Duraprogen) daily for 10 days(Tl) while group 2 got two doses of 500 mg progesterone at 5 days interval (T2). All animals were injected with1000 I.U. Folligon (PMSG) a day after progesterone withdrawal (day 12). The treatment resulted in 4-10 timesincrease in ovarian size and symptoms of estrus were exhibited in 75% and 66.6% animals in Tl and T2,respectively. The number of pregnancies that occurred in Tl and T2 were 0 and 75%, respectively. Serum sodium,potassium, calcium and phosphorus increased from day I to day 10, decreased on day 12 and again increased on day 21, which was the expected day of estrus. Calcium: Phosphorus (Ca:P) ratio also increased with progesteroneadministration.
Keywords: Hormone; Induction of Estrus; Mineral composition; Buffalo